Iqbal: an intellectual with a vision and mission (part two) - Abdul Razak, Mohd Abbas (Islam on Web (The Window to Islam), 2022)
During the many years of being a barrister, he was also actively involved in producing anthologies of poems and other philosophical works. As a poet, Iqbal was prolific in producing anthology after anthology. Although he was recognized by the world as one of the greatest Muslim poets of his time, Iqbal was humble in his admission that he was not a poet in the actual sense but merely needed poetry as a vehicle to get across his message to people. As a matter of fact, his passion for writing poems, which started from a very young age, lasted until his later years in life. His poetical works were of exceptional qualities. Unlike many other poets of his time, Iqbal did not just write his poems to lull the masses to ecstasy, but he wrote to produce a change and revolution in their mindset towards living a dignified life.